1980
DOI: 10.1017/s0033291700047413
|View full text |Cite
|
Sign up to set email alerts
|

Erythrocyte membrane cation carrier in manic-depressive psychosis

Abstract: SYNOPSISErythrocyte Na–K ATPase and sodium pump site numbers were estimated in groups of depressed, manic and recovered patients. The activity of Na–K ATPase per pump site was lower in the depressed group than in the recovered group. In the manic group Na–K ATPase was lower than that of the recovered group, whereas there was no difference in the pump site numbers. In the more severe manics the activity of Na–K ATPase per pump site was significantly lower than that of the recovered patients. Therefore, the chan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

1981
1981
2017
2017

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 55 publications
(11 citation statements)
references
References 14 publications
0
11
0
Order By: Relevance
“…However, Naylor et al (1977) failed to find any effect of lithium on Na+-K+ ATPase activity in healthy subjects, which could explain our inability to find any interaction. Though a decrease in Na+-K+ ATPase activity has been found in patients suffering from affective disorders (Naylor et al, 1980;Whalley et al, 1980) this is not a universal finding (Akagawa et al, 1980;Sengupta et al, 1980) and may be related to changes in plasma cortisol concentration (Numberger et al, 1982). Furthermore, while Naylor et al (1977) have demonstrated an increase in Na+-K+-ATPase activity in manicdepressive patients following lithium treatment this was not found by Numberger et al (1982).…”
Section: Discussionmentioning
confidence: 99%
“…However, Naylor et al (1977) failed to find any effect of lithium on Na+-K+ ATPase activity in healthy subjects, which could explain our inability to find any interaction. Though a decrease in Na+-K+ ATPase activity has been found in patients suffering from affective disorders (Naylor et al, 1980;Whalley et al, 1980) this is not a universal finding (Akagawa et al, 1980;Sengupta et al, 1980) and may be related to changes in plasma cortisol concentration (Numberger et al, 1982). Furthermore, while Naylor et al (1977) have demonstrated an increase in Na+-K+-ATPase activity in manicdepressive patients following lithium treatment this was not found by Numberger et al (1982).…”
Section: Discussionmentioning
confidence: 99%
“…Soon after the characterization of the Na + /K + ‐ATPase, some authors investigated its activity in mood disorders. These studies showed that Na + pump activity is decreased in acute mania compared to recovered euthymic bipolar individuals (Reddy et al, 1992; Hesketh et al, 1977; Naylor et al, 1980). Besides, reduced enzyme activity of Na + /K + ‐ATPase and increased intracellular sodium and calcium in erythrocytes of bipolar patients have been reported (Looney and El‐Mallakh, 1997).…”
Section: Methodsmentioning
confidence: 99%
“…Some authors have investigated the activity of Na + /K + -ATPase in mood disorders [34,35]. The model of BD and mania utilized in this study is the OUA model.…”
Section: Discussionmentioning
confidence: 99%